The mystery of Mercy Close - Keyes, Marian (London : Penguin Books, 2013)
Meet Helen, youngest of the Walsh sisters, black sheep of the family and a law unto herself. She was sacked from every job she ever had before she found her true calling as a private investigator. But times are tough for PIs and Helen's had no choice but to take on the case of missing boyband has-been Wayne Diffney.
Keywords: Boy bands -- Fiction; Detective and mystery fiction